Digital Literacy as a Primary Outcome of Blended Learning: An Explanatory Quantitative Analysis in Elementary Thematic Learning - Lalu Muktar (PT. LIB Research Cendekia, 2026)
The transformation of twenty-first-century education has intensified the integration of digital technologies not only to improve academic achievement but also to foster digital literacy as an essential learner competency. Although blended learning has been widely investigated in relation to academic performance, its relationship with strengthening elementary students' digital literacy remains underexplored and empirically unexamined. This study aimed to examine the effect of blended learning implementation on elementary school students' digital literacy within thematic learning contexts. A quantitative explanatory design was conducted with elementary students participating in a 6–8-week thematic learning cycle. Data were collected using a Digital Literacy Framework–based survey administered through a Likert-scale questionnaire and analyzed using simple linear regression. The findings revealed an increase in mean digital literacy scores from 60.1 to 82.6, with a regression coefficient of β = 0.71 (p < 0.001) and an explained variance of R² = 0.50. Improvements were consistently observed across information searching, evaluation, and utilization competencies alongside increased student engagement. The results indicate that blended learning is an effective pedagogical approach for developing digital literacy as a primary learning outcome. The study contributes theoretically by strengthening the integration of Blended Learning Theory and the Digital Literacy Framework and provides practical implications for technology-integrated instructional design in primary education